الصورة البلاغيّة في مجالس الخمر في الشعر الأمويّ - يعقوب, عبد الكريم; بيطار, لجين (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
ينشد هذا البحث الكشف عن الأبعاد النفسية لدى شعراء مجالس الخمر في العصر الأمويّ، ويعكس التطورات التي طرأت على الحياة الأمويّة، والتي جعلت الشاعر يفكّر في أمور أوسع أفقا، وأشد تعقيدا مما سبق، فكان جليّا أن تنعكس المؤثرات على الصورة البلاغيّة التي تشمل الصورة البيانيّة، والتي تبنى على التشبيه، والاستعارة، والكناية، هذه الصورة التي تنير مجالس الخمر، وتضفي عليها جمالا فنيّا متميّزا، وتفصح عن دواخل إنسانية، وتكشف عن أبعاد نفسيّة عميقة. والصورة البديعيّة التي تبنى على الطباق والجناس، وغيرهما من العناصر التي تسهم في بناء الصورة، وتشكيلها فنيّا. والدراسة نصيّة تحليلية، لا تقيّد نفسها بمنهج محدد، وإنّما تستعين بمناهج أخر تساعد في استكمال جوانب الدراسة، كالمنهج الاجتماعي، والنفسي، رغبة من الدارس في تفسير النصوص تفسيرا دقيقاً، وتأويل المعاني فيها تأويلاً سليماً. This research aims to reveal the essence of human spirit and reflect how life development during the Umayyad era broadens the horizon of poet’s thinking and makes it more sophisticated than ever. The effect of these developments is very obvious on the rhetorical image which includes simile, metaphor, and metonymy. Not only does this image illuminate drinking bouts, but it also adds distinctive artistic beauty to them. Moreover, this image discloses inner human aspects and reveals profound psychological dimensions. In addition, this image has different rhetorical devices of consonance, alliteration and other features which contribute to configuring this artistic image. This study is analytical and doesn’t adopt any specific methodology, but it uses several critical methods such as social and psychological ones to maintain unity and consistency throughout the study. All this refers to the researcher’s desire to give a clear and precise interpretation of texts and their meanings.